Hidrolisados proteicos na alimentação do jundiá (Rhamdia voulezi) em tanques-rede - Decarli, Junior Antonio (2013)
Current investigation evaluates the productive performance, carcass characteristics, chemical composition and biochemical parameters of catfish Rhamdia voulezi juveniles reared in cages and fed on diets with different meat hydrolysates. Three hundred and twenty juveniles, average initial weight 35.5 ± 0.3 g, distributed in sixteen 0.3 m3 hapas, were installed in four 4 m3 cages, in a randomized block design with four treatments and four replicates. Treatments included 60g pig liver hydrolysate/kg of diet, 40g tilapia carcass hydrolysate/kg of diet and 60g sardine hydrolysate/kg of diet. All treatments were isoproteic and isocaloric. Data were analyzed by ANOVA and then by Tukey´s test at 5% probability by SAEG statistical program. Results show that meat hydrolysates may be added to diets for the feeding of catfish